Potensi Kekayaan Dan Keberagaman Maritim Di Wilayah Papua Dalam Upaya Mendorong Kesejahteraan Rakyat - Aminuddin, Muhammad Abrar; Agussalim Burhanuddin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Indonesia, an archipelago located in Southeast Asia, has long been known as a country with tremendous maritime potential. With more than 17,000 islands stretching along the equator, Indonesia occupies a unique position as the largest archipelago in the world. Papua, as one of the provinces in Indonesia, has enormous maritime potential that offers a variety of deep and broad development opportunities. Located at the eastern tip of Indonesia, Papua has a long and diverse coastline that runs along its territory. The maritime potential in Papua includes abundant fishery resources, rich marine ecosystems, and the potential for a promising tourism sector. The research method used in this study is qualitative research. data collection method used in this study is the method of literature study. Data analysis techniques used in this study is content analysis or content analysis in which researchers use materials or literature in the form of books and journals related to the research topic. Papua has the potential to be a pioneer in sustainable economic development through the maritime sector. With prudent policies, strong collaboration, and attention to sustainability principles, Papua can harness its rich marine and mineral resources to achieve sustainable economic growth, environmental conservation, and the well-being of local communities. It is important to remember that the future of Papua lies in their own hands, with the full support of the government, private sector, and local communities, Papua can serve as an example for other regions in harnessing their maritime potential to achieve these same goals.